A Spider-Web Re-engineering Methodology for the Development of Agrarian SMEs in Zimbabwe - et. al., N Munyawarara, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The truncated development of agrarian SMEs in Zimbabwe has compelled researchers to come up with effective strategic management frameworks that promote their development.The broad objective is to determine the extent to which a spider web re-engineering methodology (SWRM) develops agrarian SMEs in Zimbabwe. A survey was conducted using a questionnaire to gather data from 100 agrarian SMEs, using purposive sampling technique. The findings revealed that there is positive relationship between a spider web re-engineering methodology and the development of agrarian SMEs. It was ascertained that agricultural SMEs are under performing due to lack of effective strategic management approaches which stimulate their radical development. Thus, the findings reveal that the development of SMEs is highly dependent on an effective SME re-engineering methodology which would contribute to transforming the SMEs into transnational companies.